Two Ideals of Educational Justice. Issue 10 (October 2016) - Stillwaggon, James
Background/Context: This essay takes up McClintock's (2004) critique of educational discourses as overly dependent upon a distributive model of justice and largely ignorant of the formative assumptions that ground educational policy and practice. Purpose/Objective: The question that McClintock's analysis begs is how educational scholarship became attached to a theoretical model that seems to fail its own requirements. My aim is to identify some of the sources of our assumptions about educational justice in order to tether them to their origins and understand how these ideological influences continue to shape our contemporary purposes Research Design: I analyze a selection of significant moments in the history of educational thought in terms of their respective contributions to one of two ideals of justice: the distributive and the formative. My aim is to show how these two long-standing ideals influence contemporary thought on educational justice and to question whether our adherence to these ideals as we have inherited them serves the needs of contemporary thinkers and the populations they seek to serve. Conclusions/Recommendations: By drawing attention to the confused status of distributive and formative ideals in education in contemporary educational discourses, the principal conclusion of this essay is that educational research's narrow reliance upon a distributive model exacts a formative injustice upon disenfranchised populations. By indicating the confusion of these ideals, we may read back critically against the commonly accepted notion of education as a democratic tool against economic injustice.